Dynamic analysis of a simple fruit tree structure model - Láng, Z. (International Journal of Horticultural Science, 2004)
The effect of shaker harvest on root damage was studied on a simple tree structure model. Equations were set up to be able to calculate the relation between shaking height and stress in the roots. To get the strain at break data field experiments were carried out. The acceleration versus time curves were recorded on different heights of the stem. Evaluating measured and calculated data it can be concluded, that the risk of root damage increases when • the height of shaking is decreased, • the stern diameter is smaller, and if • the unbalanced mass of the shaker is increased.